FDG uptake in normal tissues assessed by PET during treatment has prognostic value for treatment results in head and neck squamous cell carcinomas undergoing radiochemotherapy. Issue 3 (March 2017) - Zschaeck, Sebastian; Löck, Steffen; Leger, Stefan; Haase, Robert; Bandurska-Luque, Anna; Appold, Steffen; Kotzerke, Jörg; Zips, Daniel; Richter, Christian; Gudziol, Volker; Schreiber, Andreas; Zöphel, Klaus; et al.
Abstract: Background and purpose: Pronounced early side effects have been suggested to be a positive prognostic factor in patients undergoing chemo-radio-therapy (CRT) for head and neck squamous cell carcinomas (HNSCC). We assessed the utility of positron emission tomography (PET) during treatment to analyze the correlation of 18F-fluorodeoxyglucose (FDG) uptake in off target structures within the irradiated volume with outcome. Material and methods: Two independent cohorts of patients with locally advanced HNSCC, both treated within prospective clinical imaging trials with curatively intended CRT were retrospectively analyzed. The exploratory cohort included 50, the independent validation cohort 26 patients. Uptake of FDG in mucosa and submucosal soft tissues (MST) as well as in other structures was assessed at week 4 during treatment. Considered endpoints were local tumor control (LC) and overall survival (OS). The prognostic value of FDG uptake on the endpoints was measured by the concordance index (ci) using univariate and multivariate Cox regression analyses based on the continuous variables of the exploratory cohort. Results: In the exploratory cohort FDG uptake in MST was prognostic for LC (hazard ratio HR = 0.23, p = 0.025) and OS (HR = 0.30, p = 0.003) in univariate analyses. These findings remained significant upon multivariate testing (LC HR = 0.14, p = 0.011; OS HR = 0.20, p = 0.001) and were confirmed in the validation cohort for LC (HR = 0.15, p = 0.034) and OS (HR = 0.17, p = 0.003). Also the SUVmean threshold of MST that was generated within the exploratory cohort (2.375) yielded significant differences in OS ( p = 0.006) and a statistical trend for LC ( p = 0.078) when applied to the validation cohort. Conclusions: FDG uptake in normal tissues within the irradiated volume measured by PET during treatment has significant prognostic value in HNSCC. This effect may potentially be of use for personalized treatment adaptation.